THE EFFECTIVENESS OF ENVIRONMENTAL MONITORING ON MINERAL MINING - Usman Usman; Abrar Saleng (Universitas 17 Agustus 1945 Semarang, 2022)
This study aims to determine (1) the Implementation of Oversight of Regional Environmental Services to Mineral Mining and (2) the Effectiveness of Oversight of the Kolaka Regency Regional Environmental Service to Mineral Mining Post Law No. 23 of 2014 concerning the Regional Government. This research uses empirical research methods. The study’s chosen location was in Southeast Sulawesi, Kolaka District, and Pomalaa District. The basis for consideration of site selection because that the Kolaka Regency is one of the largest nickel mine producers in Southeast Sulawesi Province. The results showed the Implementation of Regional Environmental Services Supervision Against Mineral Mining. It focuses on Environmental Permits issued to conduct Environmental Monitoring of compliance with mineral mining business responsibility. In comparison, the Effectiveness of Supervision of Regional Environmental Services on Mineral Mining Post Law No. 23 of 2014 concerning Regional Government has not been effectively implemented by the Regional Environmental Agency through the supervision of RKL-RPL and PPLH Permits due to the facilities and facilities provided by the Environment Office to carry out supervision in the field of nickel mineral mining, not available, so it requires facilities from the parties company to carry out supervision. Supervision that must be carried out in applying environmental law requires facilities to carry out supervision effectively without affecting environmental law enforcement activities.